Electrokinetic process in soil remediation for lead removal / Ng Yee Sern - Ng, Yee Sern (2016)
Soil washing is one of the popular soil remediation methods which is widely studied for treating heavy metal contaminated land. However, this method suffers from high wash solution consumption, which eventually increases treatment cost. In order to solve this problem, a study on the incorporation of electrokinetic process into soil washing as soil remediation method was carried out, as electrokinetic process can transport metal ions using electricity in the absence of hydraulic gradient. In this study, two-stage electrokinetic washing was introduced as a novel soil remediation method in treating lead (Pb) contaminated soil at low wash solution consumption. This process consists of: i) initial soil washing to provide desorption condition in the soil, and ii) electrokinetic process to transport desorbed Pb from the soil. The study revealed that two-stage electrokinetic washing could enhance Pb removal efficiency by 4.98-20.45% in comparison to normal soil washing. Among the wash solutions, 0.1M citric acid emerged as the best wash solution as it not only yielded high removal efficiency at low power consumption compared to 0.01M NaNO3, 0.1M HNO3 and 0.01M EDTA but also maintained a stable system, low solution: soil ratio and low effluent generation. A further study on the effect of operating parameters using citric acid as the wash solution revealed that the increase in electric potential difference and wash solution concentration enhanced the removal efficiency and the interaction between these two parameters was significantly positive whereby low pH and high current density were the most important criteria in the removal process. However, unfavourable high effluent generation and power consumption were also observed under these conditions. An optimisation study on these parameters showed that an optimum removal efficiency of 84.14% with negligible extra effluent generation and low power consumption of 2.27kWh/kg Pb removed could be achieved under 7.58V and 0.057M citric acid concentration. The study proved that two-stage electrokinetic washing iv process could enhance the soil remediation efficiency by ≈16% than normal soil washing under similar low consumption of wash solution at <0.8mL:1g soil and operating conditions. Other than incorporating into soil washing, the ability of electrokinetic process as soil pretreatment method in contaminated soil volume reduction was also investigated for single Pb contaminated soil and Pb/Cr co-contaminated soil. The results showed that electrokinetic process could provide soil volume reduction by concentrating Pb and Cr into smaller soil volume in both types of soils via electromigration without hydraulic flow. The study also suggested that the performance of electrokinetic process was strongly dependent on the types of wetting agents, types of contaminants and soil conditions, whereby 0.1M citric acid was suitable for single Pb contaminated soil while 0.1M EDTA showed better performance in treating Pb/Cr cocontaminated soil. Further study on the application of approaching electrode technique in electrokinetic process revealed that this technique did not enhance the electromigration significantly in the present study. Nevertheless, approaching electrode was found to reduce the power consumption by 18% to 42% for single Pb contaminated soil and 22.5% for co-contaminated soil.